2021
DOI: 10.1002/ueg2.12154
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, epidemiology and prognosis of cholangiocarcinoma in Finland

Abstract: Background: Cholangiocarcinoma (CCA) is a cancer arising from the intra-and extrahepatic bile ducts. The early stages are often asymptomatic, CCA is frequently diagnosed in an advanced stage and the prognosis of CCA is often dismal.Objective: Our objective was to estimate the incidence of CCA in Finland and to identify risk factors for CCA, with a special interest in primary sclerosing cholangitis (PSC). Methods:We identified all CCA cases during 1974-2018 from the Finnish Cancer Registry and calculated age-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…A systematic review and meta-analysis showed that cysts and stones in the bile ducts were risk factors for ICC and ECC 6 . Moreover, a study in Mexico showed that primary sclerosing cholangitis (PSC) was a positive risk factor for developing ICC 7 , and a study in Finland also indicated that PSC was associated with both ICC and ECC 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis showed that cysts and stones in the bile ducts were risk factors for ICC and ECC 6 . Moreover, a study in Mexico showed that primary sclerosing cholangitis (PSC) was a positive risk factor for developing ICC 7 , and a study in Finland also indicated that PSC was associated with both ICC and ECC 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Another established risk factor in our study is cholelithiasis, and it also has been identified as a prominent CCA risk factor, especially for eCCA (extrahepatic CCA) in many studies (Cai et al, 2015;Clements et al, 2020;Barner-Rasmussen et al, 2021) and a possible explanation for its CCA-promoting mechanism should be the continuous chronic inflammation of bile duct caused by gallstones (Brindley et al, 2021). Furthermore, its risk effect on CCA might decline with time after cholecystectomy (Nordenstedt et al, 2012), which equals to removing the chronic inflammatory stimulus.…”
Section: Discussionmentioning
confidence: 58%
“…Also, the patient is undergoing chemotherapy as the diagnosis was made swiftly, and the patient responded positively to the treatment. One of the research projects by Barner-Rasmussen et al stated that the prevalence of the disease is comparatively more in males than females [ 12 ]. It also depends upon the patient’s age; as the patient's age increase, the chances of disease causation increase [ 13 ].…”
Section: Discussionmentioning
confidence: 99%